Organic matter chemistry controls greenhouse gas emissions from permafrost peatlands - Sjögersten, Sofie; Caul, S.; Daniell, T.J.; Jurd, A.P.S.; O'Sullivan, O.S.; Stapleton, C.S.; Titman, Jeremy J. (Elsevier, 2016)
Large tracts of arctic and subarctic peatlands are underlain by permafrost. These peatlands store large quantities of carbon (C), and are currently under severe threat from climate change. The aim of this study was to determine the size and organic chemistry of the easily degradable C pool in permafrost peatlands and link the functional organic chemistry to temperature and moisture controls of greenhouse gas emissions. First, we used a combination of field measurements and laboratory experiments to assess the influence of increased temperature and flooding on CO₂ and CH₄ emissions from sixteen permafrost peatlands in subarctic Sweden and Canada. Second, we determined the variation in organic matter chemistry and the associated microbial community composition of the peat active layer, with depth using quantitative ¹³C solid-state NMR and molecular biomarkers respectively. We demonstrate that the peat organic chemistry strongly controls CO₂ release from peat and that ca. 35 and 26% of the peat organic matter, at the Swedish and Canadian peatlands sites, respectively, is easily degradable by heterotrophic microorganisms. In contrast to CO₂, CH₄ emissions were decoupled from peat functional organic chemistry. We show a strong relationship between the microbial community structure and the peat organic chemistry suggesting that substrate type and abundance is an important driver of microbial composition in sub-arctic peatlands. Despite considerable variation in peat chemistry and microbial community composition with depth the temperature sensitivity was comparable throughout the active layer. Our study shows that functional organic chemistry controls both soil respiration rates and the composition of the microbial community. Furthermore, if these peatlands collapse and flood on thawing, they are unlikely to become large emitters of CH₄ without additional input of labile substrates.